Arrhythmia prevalence and sudden death risk in adults with the m.3243A>G mitochondrial disorder. Issue 1 (7th April 2022) - Bourke, John P; Ng, Yi Shiau; Tynan, Margaret; Bates, Matthew G D; Mohiddin, Saidi; Turnbull, Doug; Gorman, Grainne S
Abstract : Aims: To define the prevalence of non-sustained tachyarrhythmias and bradyarrhythmias in patients with the m.3243A>G mitochondrial genotype and a previously defined, profile, associated with 'high sudden-death risk'. Methods and results: Patients at high risk of sudden death because of combinations of ventricular hypertrophy, mitochondrial encephalopathy, lactic acidosis and stroke-like episodes family phenotype, epilepsy or high mutation load, due to the m.3243A>G mutation, were identified from a mitochondrial cohort of 209 patients. All recruited had serial ECG and echo assessments previously according to schedule, had an ECG-loop recorder implanted and were followed for as long as the device allowed. Devices were programmed to detect non-sustained brady- or tachy-arrhythmias. This provided comprehensive rhythm surveillance and automatic downloads of all detections to a monitoring station for cardiology interpretation. Those with sinus tachycardia were treated with beta-blockers and those with ventricular hypertrophy received a beta-blocker and ACE-inhibitor combination. Nine consecutive patients, approached (37.2±3.9 years, seven males) and consented, were recruited. None died and no arrhythmias longer than 30s duration occurred during 3-year follow-up. Three patients reported palpitations but ECGs correlated with sinus rhythm. One manifest physiological, sinus pauses >3.5 s during sleep and another had one asymptomatic episode of non-sustained ventricular tachycardia. Conclusions: Despite 'high-risk' features for sudden death, those studied had negligible prevalence of arrhythmias over prolonged follow-up. By implication, the myocardium in this genotype is not primarily arrhythmogenic. Arrhythmias may not explain sudden death in patients without Wolff-Parkinson-White or abnormal atrioventricular conduction or, it must require a confluence of other, dynamic, proarrhythmic factors to trigger them.